INTERAKSI SOSIAL ANTARA SISWA REGULER DENGAN BERKEBUTUHAN KHUSUS DALAM MENINGKATKAN MOTIVASI BELAJAR (Studi Kasus di MIT Ar-Roihan Lawang – Malang) - Khusnul Isma Nuriza (Universitas Islam Raden Rahmat Malang, 2023)
The Social interaction is an important and absolute thing in MIT Ar-Roihan which is an inclusive school. There are students who have difficulty in social interaction with their friends, so it influences their learning motivation. This can be seen from the action of regular students who still make